Rapid hearing threshold assessment with modified auditory brainstem response protocols in dogs - Stanger, Axel; Buhmann, Gesine; Dörfelt, Stefanie; Zablotski, Yury; Fischer, Andrea (Frontiers in Veterinary Science, 2024)
Introduction: Auditory Brainstem Response (ABR) is the gold standard for hearing testing in dogs. ABR is commonly used in puppies to diagnose congenital sensorineural deafness. Long test times limit the use for a more comprehensive hearing screening in veterinary practice.This study aimed to establish a super-fast hearing screening protocol in dogs.Methods: Hearing thresholds were routinely measured with a mobile device designed for newborn hearing screening in 90 dogs. We introduced modifications of the ABR protocol, e. g., a binaural test mode, higher stimulus rates, a broadband Chirp stimulus, and an algorithm for automatic peak V detection in a stepwise fashion. Hearing thresholds were then measured with fast protocols utilizing either 30 Hz Click or 90 Hz broadband chirp stimuli with 80, 60, 40, 30, 20, 10, 0 and -10 dBnHL stimulation intensities. Interrater reliability, agreement between Click and Chirp hearing thresholds and correlations with clinical characteristics of the dogs were assessed.Results: Using all innovations, the test time for hearing threshold assessment in both ears was reduced to 1.11 min (mean). The Chirp stimulus accentuated both, peak V and the subsequent trough, which are essential features for judgement of the hearing threshold, but preceding peaks were less conspicuous. Interrater reliability and agreement between Click and Chirp hearing threshold was excellent. Dogs > 10 years of age and dogs with abnormal hearing score or otitis score had significantly higher hearing thresholds than younger dogs (p ≤ 0.001) or dogs without abnormalities (p < 0.001).Conclusions: The results demonstrate that modifications in ABR protocols speed-up test times significantly while the quality of the recordings for hearing threshold assessment is maintained. Modified ABR protocols enable super-fast hearing threshold assessment in veterinary practice.